Patient’s satisfaction with clinical laboratory services in a tertiary health care hospital of Jammu and Kashmir, India - Kumar Sharma, Rakesh; Bhardwaj, Subhash; Mahajan, Surbhi (International Journal Of Community Medicine And Public Health, 2023)
Background: A patient’s satisfaction level is a crucial aspect of quality management in clinical laboratories. Satisfaction is the client’s perception of care received compared with the care expected. Accreditation from an organization such as NABL or NABH is necessary. This study aimed to evaluate patient satisfaction with laboratory services in a tertiary care hospital in Jammu, UT of Jammu and Kashmir, India. Methods: The study conducted a prospective cross-sectional patient satisfaction survey over six months w.e.f. April 2022 to September 2022 at 05 patients/day with monthly data (05×30=150). A total of 900 patients were selected randomly at 150 patients/month (150×6=900). Data was collected using structured questionnaire, entered in Epi Info and analysed with SPSS software. A p value of less than 0.05 was taken as statistically significant. Results: The study found that 76.55% of patients were satisfied, while 11% were mildly dissatisfied and 17.94% were dissatisfied with laboratory services. Patients were dissatisfied with cleanliness of latrines (47%), long waiting times (30%), clear and understandable advisory service during specimen collection (26%), adequacy of waiting area (25%), easy accessibility of laboratory (19%), latrine location (20%), availability of requested service (18%), unfair payment of service (17%), and missing results (12%). Conclusions: The study concluded that despite most patients being satisfied, there were gaps. The study recommends that the concerned departments to improve the identified gaps and meet patients’ needs. Educational status and distance were found to be significantly associated with the overall satisfaction level of clients.